Elizabeth May on the spruce budworm - Memorial University of Newfoundland. Extension Service (Producer)
In this tape Elizabeth May gives a presentation by the Cape Breton Land Owners in which they outline the basis of their opposition to the government's proposed spray program. Audio and video are out of synch